An investigation of foreign language writing anxiety and its reasons among pre-service EFL teachers in Pakistan - Rasool, Ushba; Qian, Jiancheng; Aslam, Muhammad Zammad (Frontiers in Psychology, 2023)
Psychologically complicated by nature, anxiety refers to feelings of worry, fear, or apprehension. Several research studies have been devoted to exploring anxiety's effects on language skills, including writing. Since foreign language anxiety directly influences a learner's motivation and determination to learn that language, it is imperative to study the findings and reasons behind these anxious feelings. One-third of foreign language learners have been experiencing at least a moderate level of anxiety. Researchers have attempted to investigate the causes of anxiety among foreign language pre-service teachers. The present study objectifies two goals to determine the extent of writing anxiety, followed by reasons and references to the role of gender. Seventy-two pre-service teachers of the English language training department from the University of Education, Multan, Pakistan, were selected for the study using convenience sampling. Second language writing anxiety inventory (SLWAI) and second language writing anxiety reasons inventory (SLWARI) were used to collect data, and semi-structured interviews were taken with students. The findings presented no difference in anxiety levels between genders, whereas cognitive anxiety type was distinctive in results. Most of the participants experienced high and medium levels of anxiety.